2016
DOI: 10.1111/jpn.12519
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between level of forage intake, blood flow and oxygen consumption by splanchnic tissues of sheep fed a tropical grass forage

Abstract: Four Polwarth castrated male sheep (42 ± 4.4 kg live weight (LW) surgically implanted with chronic indwelling catheters into the mesenteric, portal and hepatic veins, housed in metabolism cages and offered Cynodon sp. hay at rates (g of dry matter (DM)/kg LW) of 7, 14, 21 or ad libitum, were used in a 4 × 4 Latin square experiment to evaluate the effect of the level of forage intake on blood flow and oxygen consumption by the portal-drained viscera (PDV), liver and total splanchnic tissues (ST). The portal blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The ST contributes a high proportion of whole‐animal energy expenditure accounting for up to 50% of the total oxygen consumption (Huntington, ; Johnson, Johnson, & Baldwin, ). In the present study, by extrapolating the O 2 consumption to a 24‐hr period, and taking into account a heat equivalent of 4.89 kcal/L of O 2 uptake (Huntington & Tyrrell, ), the heat produced by liver and ST was on average 6 and 14 kcal/kg BW representing 16% and 38% of the ME intake, respectively, values in agreement with previews findings (El‐Sabagh, Goto, Sugino, Obitsu, & Taniguchi, ; Hentz, Kozloski, Zeni, Brun, & Stefanello, ). Moreover, glucose and urea synthesis are among the most energetically demanding processes in liver (McBride & Kelly, ).…”
Section: Discussionsupporting
confidence: 91%
“…The ST contributes a high proportion of whole‐animal energy expenditure accounting for up to 50% of the total oxygen consumption (Huntington, ; Johnson, Johnson, & Baldwin, ). In the present study, by extrapolating the O 2 consumption to a 24‐hr period, and taking into account a heat equivalent of 4.89 kcal/L of O 2 uptake (Huntington & Tyrrell, ), the heat produced by liver and ST was on average 6 and 14 kcal/kg BW representing 16% and 38% of the ME intake, respectively, values in agreement with previews findings (El‐Sabagh, Goto, Sugino, Obitsu, & Taniguchi, ; Hentz, Kozloski, Zeni, Brun, & Stefanello, ). Moreover, glucose and urea synthesis are among the most energetically demanding processes in liver (McBride & Kelly, ).…”
Section: Discussionsupporting
confidence: 91%
“…The liver and kidneys have a central role in the metabolism of organic acids and dietary protein and may have hypertrophied to process the greater flow of these compounds in the body of the animals fed with cactus (Hentz et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, it worth noting that despite improving the ratio of concentrate to forage (F: C) can increase the levels of weight gain and/or efficiency of gain, there may be a change in the metabolic state of animals [ 2 ]. Previous studies have reported that dietary nutrient levels such as F: C significantly affected animal metabolic activities [ 3 , 4 ]. Research has consistently shown that feeding a high concentrate diet in ruminants can lead to rapid fermentation and subsequent excessive organic acid accumulation.…”
Section: Introductionmentioning
confidence: 99%